Lithium iron silicon niobium oxygen composite positive electrode material, preparation method and application thereof

CN122501870BActive Publication Date: 2026-10-16ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610995469.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-16
Estimated Expiration
2046-07-06

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种锂铁硅铌氧复合正极材料及其制备方法和应用,解决了富锂铁酸锂结构稳定性较差的技术问题

Benefits of technology

[0012] This invention provides a method for preparing a lithium iron silicon niobium oxygen composite cathode material, comprising mixing lithium ferrite, silicon source, and niobium source uniformly in a certain molar ratio and then calcining them under an inert gas atmosphere to obtain a lithium iron silicon niobium oxygen crystalline compound, wherein the lithium iron silicon niobium oxygen crystalline compound is subjected to high-energy ball milling to obtain an amorphous lithium iron silicon niobium oxygen composite cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122501870B_ABST
    Figure CN122501870B_ABST
Patent Text Reader

Abstract

The application provides a lithium-iron-silicon-niobium-oxygen composite positive electrode material and a preparation method and application thereof, relates to the technical field of composite materials, and the preparation method of the lithium-iron-silicon-niobium-oxygen composite positive electrode material comprises the following steps: uniformly mixing lithium ferrite, a silicon source and a niobium source according to a certain molar ratio, and then calcining under an inert gas atmosphere to obtain a lithium-iron-silicon-niobium-oxygen crystal compound; and the lithium-iron-silicon-niobium-oxygen crystal compound is subjected to high-energy ball milling treatment to obtain the lithium-iron-silicon-niobium-oxygen composite positive electrode material. The lithium-iron-silicon-niobium-oxygen composite positive electrode material prepared has relatively high capacity, cycle performance and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, specifically to lithium iron silicon niobium oxygen composite cathode materials, their preparation methods, and applications. Background Technology

[0002] Rechargeable lithium metal batteries, with their ultra-high energy density, are widely recognized as a crucial development direction for next-generation power batteries and energy storage systems. Constructing high-energy-density lithium metal batteries urgently requires the development of novel cathode materials with low cost and high specific capacity. Lithium iron oxide compounds (Li5FeO4), with their orthogonal anti-fluorite structure, have a high lithium content per mole, and their theoretical specific capacity can reach up to 800 mAh / g. Furthermore, iron resources are inexpensive, making them a potential high-specific-capacity cathode material. However, research on their electrochemical reactions has revealed several drawbacks: ① Li5FeO4 crystals exhibit poor structural stability, undergoing an irreversible phase transition and oxygen evolution during the first charge-discharge cycle, leading to structural collapse and preventing lithium ion re-intercalation, resulting in a large irreversible capacity. ② Lithium iron oxide is an alkaline compound, prone to water absorption and deterioration, and has poor air stability. ③ During long-term battery cycling, the decomposition product of structurally unstable lithium iron oxide, iron oxide, can be reduced to iron crystals, causing battery safety malfunctions and other application challenges. Therefore, at present, lithium iron ferrite, rich in lithium, can only be used as a lithium supplement agent in the positive electrode material of lithium batteries by taking advantage of its high lithium content.

[0003] To improve the application function of lithium-rich lithium iron ferrite supplements, a series of publicly available technologies have been developed. For example, Chinese patent application CN121439799A discloses a method for preparing a gradient-doped monolayer coated lithium-rich lithium iron ferrite material. This method involves pretreating the Li5FeO4 core using a ball milling process, followed by gradient doping and coating using a dynamic CVD method. This ultimately yields a gradient-doped monolayer coated lithium iron ferrite material, improving the air stability and ionic conductivity of the lithium-rich lithium iron ferrite supplement. (Chinese patent application C...) N121662994A also discloses a method for preparing a bifunctional composite lithium supplement additive, using lithium-rich lithium iron ferrite (Li5FeO4) as the core layer, and coating its surface with lanthanum gallate (LaGaO3) through ball milling and calcination to form a core-shell structure as a composite lithium supplement agent, thereby improving its air stability; CN119361866A discloses a carbon-aluminate double-layer coated lithium-rich lithium iron ferrite, its preparation method and application, which optimizes lithium supplement performance and cycle life through double-layer coating modification, and improves the material's structural integrity and electronic conductivity.

[0004] The above-mentioned improvement methods can improve the air stability and ionic conductivity of lithium iron ferrite, but they do not significantly improve the structural stability of lithium iron ferrite. As a result, its cycle charge and discharge performance is still poor when used as a positive electrode material, and it cannot meet the high-rate long-cycle performance requirements of lithium batteries. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a lithium iron silicon niobium oxygen composite cathode material, its preparation method, and its application, solving the technical problem of poor structural stability of lithium iron oxide.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] The first aspect of this invention provides a method for preparing a lithium iron ferrite silicon niobium oxygen composite cathode material, comprising mixing lithium ferrite, silicon source, and niobium source uniformly in a certain molar ratio and then calcining them under an inert gas atmosphere to obtain a lithium iron ferrite silicon niobium oxygen crystal compound, wherein the lithium iron ferrite silicon niobium oxygen crystal compound is subjected to high-energy ball milling to obtain the lithium iron ferrite silicon niobium oxygen composite cathode material.

[0008] The second aspect provides a lithium iron silane niobium oxide composite cathode material prepared by the aforementioned preparation method, wherein the nominal composition of the lithium iron silane niobium oxide composite cathode material is Li5(Fe 0.75+y Si 0.1+x Nb x O4, where 0.03≤x≤0.07, y=0.15-2x;

[0009] The lithium iron silicon niobium oxide composite cathode material includes amorphous lithium iron silicon niobium oxide compound and lithium niobate nanocrystals, wherein the amorphous lithium iron silicon niobium oxide compound accounts for >95%.

[0010] In a third aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising the aforementioned lithium iron silicon niobium oxygen composite positive electrode material.

[0011] Compared with existing technologies, it has the following beneficial effects:

[0012] This invention provides a method for preparing a lithium iron silicon niobium oxygen composite cathode material, comprising mixing lithium ferrite, silicon source, and niobium source uniformly in a certain molar ratio and then calcining them under an inert gas atmosphere to obtain a lithium iron silicon niobium oxygen crystalline compound, wherein the lithium iron silicon niobium oxygen crystalline compound is subjected to high-energy ball milling to obtain an amorphous lithium iron silicon niobium oxygen composite cathode material.

[0013] In the lithium-iron silicon-niobium-oxygen composite cathode material prepared by the above method, strong covalent bonds are formed between silicon and oxygen, improving structural stability and suppressing irreversible phase transitions and oxygen precipitation. A small amount of pentavalent niobium ions with radii similar to trivalent iron ions are embedded in the crystal lattice. The strong chemical bonds between pentavalent niobium ions and oxygen atoms pin the surrounding oxygen atoms and iron ions, suppressing iron ion displacement during delithiation and further improving crystal structure stability. More importantly, while the strong covalent bonds between silicon and oxygen suppress oxygen release, the effective ionic radius of silicon in the silicon-oxygen tetrahedral structure is too small. Introducing a large amount of silicon will cause crystal structure deformation, generating excessive internal stress and losing crystal stability. Correspondingly, the replacement of trivalent iron with pentavalent niobium ions, and the large-scale introduction of pentavalent niobium, will cause an imbalance in the chemical bonds between niobium, iron ions, and oxygen atoms, leading to lattice distortion and inducing iron ion or oxygen atom displacement in the lattice, blocking lithium ion diffusion channels and exacerbating structural disorder. Therefore, excessive tetravalent silicon or pentavalent niobium will cause a sharp decline in the rate capability, capacity, and cycle performance of the lithium-iron silicon-niobium-oxygen composite cathode material. In the preparation of lithium iron silicon niobium oxide composite cathode materials, the molar ratio of total molar amount of silicon dioxide and niobium pentoxide to lithium iron oxide is 0.15-0.30:1. With the synergistic effect of the molar ratio of silicon dioxide and niobium pentoxide being 1:0.12-0.20, a balance can be achieved between the strong oxygen-fixing ability of silicon and the excessive internal stress caused by the small effective ionic radius of silicon, and between the framework support ability of niobium and the lattice distortion. This improves the structural stability of lithium iron silicon niobium oxide crystals, and the prepared lithium iron silicon niobium oxide composite cathode materials have better capacity, cycle performance and rate performance. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 This is the XRD pattern of lithium iron ferrite A (original phase) prepared in Example 1.

[0016] Figure 2 The Li5Fe prepared in Example 1 0.8 Si 0.15 Nb 0.05 XRD pattern of O4 crystalline compound B1.

[0017] Figure 3 The Li5Fe prepared in Example 1 0.8 Si 0.15 Nb 0.05Local magnified XRD patterns of O4 crystal compound B1 and lithium iron ferrite A.

[0018] Figure 4 The lithium iron silicon niobium oxygen composite cathode material (Li5Fe) prepared in Example 1 is shown. 0.8 Si 0.15 Nb 0.05 XRD pattern of C1 powder (O4).

[0019] Figure 5 The lithium iron silicon niobium oxygen composite cathode material (Li5Fe) prepared in Example 1 is shown. 0.8 Si 0.15 Nb 0.05 SEM image and EDS spectrum of O4 powder C1.

[0020] Figure 6 The lithium iron silicon niobium oxygen composite cathode material (Li5Fe) prepared in Example 2 is shown. 0.84 Si 0.13 Nb 0.03 XRD pattern of C2 powder (O4).

[0021] Figure 7 The lithium iron silicon niobium oxygen composite cathode material (Li5Fe) prepared in Example 3 is shown. 0.76 Si 0.17 Nb 0.07 XRD pattern of C3 powder (O4).

[0022] Figure 8 The capacity retention rate of a coin cell prepared from the composite cathode materials C1 and D1 prepared in Example 1 and Comparative Example 8 after 400 cycles at 5C rate is shown.

[0023] Figure 9 The capacity retention rate of a full cell prepared from the composite cathode materials C1 and D1 prepared in Example 1 and Comparative Example 8 after 2000 cycles at a 7.5C rate is shown. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] This application provides a lithium iron silicon niobium oxygen composite cathode material, its preparation method, and its application, which solves the technical problem of poor structural stability of lithium iron oxide and achieves better cycle charge-discharge performance.

[0026] The technical solution in this application is to solve the above-mentioned technical problems, and the general idea is as follows:

[0027] The first aspect of this invention provides a method for preparing a lithium iron phosphate (LiFePO4)-silicon-niobium-oxygen (NiO2) composite cathode material, comprising mixing lithium ferrite, a silicon source, and a niobium source uniformly in a certain molar ratio and then calcining them under an inert gas atmosphere to obtain a LiFePO4-silicon-niobium-oxygen crystalline compound. In the LiFePO4-silicon-niobium-oxygen crystalline compound, silicon and niobium replace some of the iron sites, forming a single-phase crystalline compound. The LiFePO4-silicon-niobium-oxygen crystalline compound is then subjected to high-energy ball milling to obtain an amorphous LiFePO4-silicon-niobium-oxygen composite cathode material. The amorphous LiFePO4-silicon-niobium-oxygen composite cathode material has small particles, which reduces the resistance of lithium ions entering the LiFePO4-silicon-niobium-oxygen composite cathode material during battery charge-discharge cycles, thereby improving the cycle performance of the battery. As a preferred technical solution, the silicon source is silicon dioxide, the niobium source is niobium pentoxide, and the molar ratio of the total molar amount of silicon dioxide and niobium pentoxide to lithium iron oxide is 0.15-0.30:1, for example, it can be 0.15:1, 0.17:1, 0.22:1, 0.27:1, 0.30:1 or any value between them; the molar ratio of silicon dioxide to niobium pentoxide is 1:0.12-0.20, for example, it can be 1:0.12, 1:0.17, 1:0.20 or any value between them.

[0028] The lithium iron silane niobium-oxygen composite cathode material prepared by the above method exhibits strong covalent bonds formed by silicon and oxygen, improving structural stability and suppressing irreversible phase transitions and oxygen precipitation. A small number of pentavalent niobium ions with radii similar to trivalent iron ions are embedded in the crystal lattice. The strong chemical bonds between the pentavalent niobium ions and oxygen atoms pin the surrounding oxygen and iron atoms, suppressing their displacement during delithiation and further enhancing crystal structure stability. Furthermore, because the oxygen atoms are pinned by niobium ions, an oxygen layer cannot form on the surface of the cathode material during delithiation, reducing the resistance to lithium ion entry into the lithium iron silane niobium-oxygen composite cathode material during battery charge-discharge cycles and improving the battery's cycle performance and rate performance. As a preferred embodiment, the silicon source is silicon dioxide, the niobium source is niobium pentoxide, and the molar ratio of the total molar amount of silicon dioxide and niobium pentoxide to lithium iron ferrite is 0.15-0.30:1, and the molar ratio of silicon dioxide to niobium pentoxide is 1:0.12-0.20. With the synergistic effect of a total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite of 0.15-0.30:1 and a molar ratio of silicon dioxide to niobium pentoxide of 1:0.12-0.20, the lithium iron silicon niobium oxygen composite cathode material achieves a balance between the strong oxygen-fixing ability of silicon and the excessive internal stress caused by the small effective ionic radius of silicon, and between the framework support ability of niobium and the lattice distortion of niobium. This improves the structural stability of the lithium iron silicon niobium oxygen composite cathode material, and the prepared lithium iron silicon niobium oxygen composite cathode material has better capacity, cycle performance and rate performance.

[0029] Preferably, the silicon dioxide is amorphous SiO2 with a particle size of 10-100 nm, for example, the particle size can be 10 nm, 50 nm, 80 nm, 100 nm or any value between them, and the specific surface area is 90-400 m². 2 / g, for example, the specific surface area can be 90m² 2 / g, 150m 2 / g、200m 2 / g、250m 2 / g、300m 2 / g, 350m 2 / g、400m 2 / g or any value therebetween. This structure allows for closer contact between silica and lithium ferrite particles, and a shorter diffusion distance between reactants, which helps to generate crystalline lithium iron silicon niobium oxide with a purer phase and a more uniform elemental distribution.

[0030] Preferably, the niobium pentoxide particle size D50 is 1800-2600 nm, for example, the particle size can be 1800 nm, 2000 nm, 2300 nm, 2600 nm or any value between them, and the specific surface area is 0.50-0.73 m². 2 / g, for example, the specific surface area can be 0.5m². 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.71m 2 / g, 0.73m 2 / g or any value in between.

[0031] Preferably, the lithium ferrite is Li5FeO4.

[0032] Preferably, the high-energy ball milling process includes: rotating at a speed of 500-700 r / min clockwise for 4-8 min, resting for 2-5 min, then rotating at 500-700 r / min counterclockwise for 4-8 min, resting for 2-5 min, alternating between these two processes, for a total milling time of 30-50 h; the ball-to-material ratio is 20-40:1 by mass. Under these conditions, an amorphous phase ratio greater than 95% is prepared, with a small amount of LiNbO present. x High-stability, high-capacity lithium-iron-silicon-niobium-oxygen composite cathode material with nanocrystals.

[0033] Secondly, the present invention provides a lithium iron silicon niobium oxygen composite cathode material prepared by the aforementioned preparation method, wherein the nominal composition of the lithium iron silicon niobium oxygen composite cathode material is Li5(Fe 0.75+y Si 0.1+x Nb xThe lithium iron silicon niobium oxide composite cathode material comprises amorphous lithium iron silicon niobium oxide compound and lithium niobate nanocrystals, wherein the amorphous lithium iron silicon niobium oxide compound accounts for >95%. The fine amorphous lithium iron silicon niobium oxide compound particles can shorten the diffusion distance of lithium ions and electrons, improving ion conductivity. x Nanocrystals can significantly enhance ion conductivity, therefore, lithium iron silicon niobium oxygen composite cathode materials have excellent ion conductivity.

[0034] In a third aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising the aforementioned lithium iron silicon niobium oxygen composite positive electrode material.

[0035] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.

[0036] I. Preparation Method

[0037] Example 1

[0038] This embodiment provides a method for preparing a lithium iron silicon niobium oxygen composite cathode material, including the following steps:

[0039] S1. Mix ferric oxide and lithium oxide powder according to n 氧化锂 :n 三氧化二铁 The lithium oxide powder was weighed out in a ratio of 5.2:1, that is, 1.02 g of lithium oxide and 1.04 g of ferric oxide powder were placed in a ball mill jar and mixed. The mixture was stirred at 300 r / min for 12 h, and then calcined at 550 °C for 8 h under an argon atmosphere to obtain lithium iron ferrite A.

[0040] S2. Weigh and mix the raw materials according to the molar ratio of lithium iron ferrite A powder, silicon dioxide powder, and niobium pentoxide powder of 8:1.5:0.25 to obtain a mixed powder. The mixed powder is then ball-milled in a planetary ball mill at 300 r / min for 12 h, and then calcined at 700℃ for 12 h under an argon atmosphere to obtain Li5Fe. 0.8 Si 0.15 Nb 0.05 O4 crystalline compound B1. The niobium pentoxide powder has a particle size D50 of 2000 nm and a specific surface area of ​​0.6 m². 2 / g.

[0041] S3, the above Li5Fe 0.8 Si 0.15 Nb 0.052g of O4 crystal compound B1 powder was loaded into a 50ml ball mill jar of a high-energy ball mill with a ball-to-powder ratio of 30:1 (mass ratio). The ball milling was carried out by alternating between forward rotation for 5min-600r / min, resting for 2min, and then reverse rotation for 5min-600r / min, resting for 2min, for a total milling time of 40h, to obtain lithium iron silicon niobium oxygen composite cathode material powder C1.

[0042] Lithium iron oxide A, intermediate Li5Fe 0.8 Si 0.15 Nb 0.05 The structural tests of O4 crystalline compound B1 and lithium iron silicon niobium oxide composite cathode material powder C1 are shown in [the table]. Figures 1-6 .

[0043] like Figure 1 The XRD pattern of lithium iron ferrite A shows that it is consistent with the PDF card of standard Li5FeO4, indicating that the prepared lithium iron ferrite A has excellent phase purity.

[0044] Figure 2 Li5Fe 0.8 Si 0.15 Nb 0.05 The XRD pattern of O4 crystal compound B1, compared with the standard PDF card, shows that the main phase of intermediate compound B1 is still an orthorhombic antifluorite crystal of Li5FeO4, with a small amount of LiNbO as an accompanying component. x The presence of a crystalline phase indicates that after the S2 process, Si and some Nb replaced Fe lattice sites in the form of a solid solution and entered the Li5FeO4 lattice.

[0045] Figure 3 Li5Fe 0.8 Si 0.15 Nb 0.05 Local magnified XRD patterns of O4 crystal compound B1 and lithium iron ferrite A were compared, based on the intermediate Li5Fe 0.8 Si 0.15 Nb 0.05 A comparison of the characteristic peaks of O4 crystal compound B1 and lithium iron ferrite A shows that the strongest diffraction peak of intermediate compound B1 (222) shifts to a higher angle direction by 0.05°. According to the Bragg equation, the corresponding interplanar spacing decreases, confirming that intermediate Li5Fe 0.8 Si 0.15 Nb 0.05 In the O4 crystal compound B1, the doped Si and Nb elements partially replace the Fe in the crystal lattice, that is, Si-O and Nb-O bonds have been formed in the crystal lattice.

[0046] Figure 4 Li5Fe is an intermediate.0.8 Si 0.15 Nb 0.05 The lithium-iron-silicon-niobium-oxygen composite cathode material (Li5Fe) obtained after the O4 crystalline compound B1 is amorphized is obtained. 0.8 Si 0.15 Nb 0.05 The XRD pattern of C1 powder (O4) shows a significant disappearance of the crystallization diffraction peaks, corresponding to LiNbO. x The characteristic peaks of crystallization are also very weak, especially the broadened bulge peaks corresponding to the amorphous state appearing around 20-30°. Calculations using the peak and baseline functions in Origin software showed that the proportion of the amorphous portion was greater than 95%. The specific method is as follows: In Origin software, the baseline of the entire XRD curve is determined using the peak and baseline functions, ensuring that all characteristic peaks are above the curve baseline. Then, the curve integration function is used to integrate the curve region containing the characteristic peaks. The area obtained by integrating this integral with the area obtained by integrating the entire XRD curve is compared to obtain the proportion of the crystallized portion. Subtracting this proportion from 1 gives the proportion of the amorphous portion.

[0047] Figure 5 It is a lithium iron silicon niobium oxygen composite cathode material (Li5Fe 0.8 Si 0.15 Nb 0.05 SEM images and EDS analysis of O4) powder C1 show that the lithium iron silicon niobium oxygen composite cathode material (Li5Fe) 0.8 Si 0.15 Nb 0.05 O4)Cl consists of spherical secondary particles with a diameter of less than 5 micrometers. The Fe, O, Si and Nb elements are uniformly distributed in the spherical secondary particles. Quantitative analysis shows that the atomic ratio of Fe, Si and Nb is close to 0.8:0.15:0.05.

[0048] Example 2

[0049] The difference between this embodiment and Embodiment 1 is that in S2, each raw material is weighed according to the molar ratio of lithium iron ferrite A, silicon dioxide, and niobium pentoxide powder of 8.4:1.3:0.15. The mixed powders are ball-milled and mixed evenly in a planetary ball mill and then heat-treated to prepare the intermediate Li5Fe. 0.84 Si 0.13 Nb 0.03 O4 crystal compound B2, otherwise the same as in Example 1, the prepared lithium iron silicon niobium oxygen composite cathode material powder is denoted as C2.

[0050] Figure 6 The XRD pattern of C2, the lithium iron silicon niobium oxygen composite cathode material powder in Example 2, also shows a broadened bulge peak near 20°. The comparison with the intensity of the residual crystallization characteristic peak indicates that the material C2 has achieved amorphization modification, and its amorphization degree reaches 95%.

[0051] Example 3

[0052] The difference between this embodiment and Embodiment 1 is that in S2, each raw material is weighed according to the molar ratio of lithium iron ferrite A, silicon dioxide, and niobium pentoxide powder of 7.6:1.7:0.35. The mixed powders are ball-milled in a planetary ball mill to prepare intermediate Li5Fe by heat treatment. 0.76 Si 0.17 Nb 0.07 O4 crystal compound B3, otherwise the same as in Example 1, the prepared lithium iron silicon niobium oxygen composite cathode material powder is denoted as C3.

[0053] Figure 7 The XRD pattern of the lithium iron silicon niobium oxygen composite cathode material powder C3 in Example 3 shows a broadened bulge peak near 20°. The comparison with the intensity of the residual crystallization characteristic peak indicates that the material C3 has achieved amorphization modification, and its amorphization degree reaches 95%.

[0054] Comparative Example 1

[0055] This comparative example provides a method for preparing a lithium iron niobium oxide composite cathode material. The difference from Example 1 is that in step S2, each raw material is weighed according to a molar ratio of lithium iron ferrite A powder to niobium pentoxide powder of 8:1. The mixed powders are ball-milled in a planetary ball mill until homogeneous and then heat-treated to prepare a composite cathode material with Li5FeO4 as the main phase. Other steps are the same as in Example 1.

[0056] The final lithium iron niobium oxygen composite cathode material was confirmed by XRD testing to be an amorphous compound.

[0057] Comparative Example 2

[0058] This comparative example provides a method for preparing a lithium iron phosphate silicon oxide composite cathode material. The difference from Example 1 is that in S2, each raw material is weighed according to a molar ratio of lithium iron phosphate A powder to silicon dioxide powder of 8:2. The mixed powders are ball-milled in a planetary ball mill until homogeneous, and then heat-treated to prepare the intermediate Li5Fe. 0.8 Si 0.2 O4 crystalline compound. Other aspects are the same as in Example 1.

[0059] Comparative Example 3

[0060] This comparative example provides a method for preparing a lithium iron cobalt oxide composite cathode material. The difference from Example 1 is that in S2, each raw material is weighed according to the molar ratio of lithium iron phosphate A powder and CoO of 8:2. The mixed powder is ball-milled and mixed evenly in a planetary ball mill and then heat-treated to prepare a composite cathode material with Li5FeO4 as the main phase. The rest is the same as in Example 1. The lithium iron cobalt oxide composite cathode material is confirmed to be an amorphous compound by XRD test results.

[0061] Comparative Example 4

[0062] This comparative example provides a method for preparing a lithium iron phosphate silicon niobium oxide composite cathode material. The difference from Example 1 is that in step S2, each raw material is weighed and mixed according to a molar ratio of lithium iron phosphate A powder, silicon dioxide powder, and niobium pentoxide powder of 8.8:0.9:0.15. The mixed powder is then ball-milled in a planetary ball mill until homogeneous, followed by heat treatment to prepare the intermediate Li5Fe. 0.88 Si 0.09 Nb 0.03 O4 crystalline compound. Other aspects are the same as in Example 1.

[0063] Comparative Example 5

[0064] This comparative example provides a method for preparing a lithium iron phosphate silicon niobium oxide composite cathode material. The difference from Example 1 is that in step S2, the raw materials are weighed and mixed according to a molar ratio of lithium iron phosphate A powder, silicon dioxide powder, and niobium pentoxide powder of 7.4:1.95:0.325. The mixed powders are then ball-milled in a planetary ball mill until homogeneous and subjected to heat treatment to prepare the intermediate Li5Fe. 0.74 Si 0.195 Nb 0.065 O4 crystalline compound. Other aspects are the same as in Example 1.

[0065] Comparative Example 6

[0066] This comparative example provides a method for preparing a lithium iron phosphate silicon niobium oxide composite cathode material. The difference from Example 1 is that in S2, the raw materials are weighed and mixed according to a molar ratio of lithium iron phosphate A powder, silicon dioxide powder, and niobium pentoxide powder of 8:1.2:0.4. The mixed powders are then ball-milled in a planetary ball mill until homogeneous and subjected to heat treatment to prepare the intermediate Li5Fe. 0.8 Si 0.12 Nb 0.08 O4 crystalline compound. Other aspects are the same as in Example 1.

[0067] Comparative Example 7

[0068] This comparative example provides a method for preparing a lithium iron phosphate silicon niobium oxide composite cathode material. The difference from Example 1 is that in step S2, each raw material is weighed and mixed according to a molar ratio of lithium iron phosphate A powder, silicon dioxide powder, and niobium pentoxide powder of 8:1.7:0.15. The mixed powder is then ball-milled in a planetary ball mill until homogeneous, followed by heat treatment to prepare the intermediate Li5Fe. 0.8 Si 0.17 Nb 0.03 O4 crystalline compound. Other aspects are the same as in Example 1.

[0069] Comparative Example 8

[0070] This comparative example provides a method for preparing amorphous lithium iron phosphate cathode material, comprising the following steps:

[0071] S1. 1.04 g of ferric oxide and 1.02 g of lithium oxide powder were placed in a planetary ball mill and mixed at 300 r / min for 12 h. Then, they were calcined at 550 °C for 8 h under an argon atmosphere to obtain lithium iron ferrite A.

[0072] S2. Place 2 g of lithium iron ferrite A into a 50 ml ball mill jar of a high-energy ball mill and ball mill it. The ball-to-material ratio is 30:1 (mass ratio). Set the rotation speed to 5 min-600 r / min in the forward direction, let it stand for 2 min, then rotate it in the reverse direction for 5 min-600 r / min, let it stand for 2 min, and repeat the process. The total ball milling time is 40 h to obtain amorphous lithium iron ferrite D1.

[0073] Battery manufacturing

[0074] 1. The composite cathode material prepared using the examples and comparative examples is used to prepare coin cells. The specific method is as follows:

[0075] Step 1: Place 0.75 g of the prepared composite cathode material, 0.19 g of super black material, 0.01 g of carbon nanotubes (CNTs), and 0.05 g of polytetrafluoroethylene (PTFE) into a planetary ball mill and mix at 300 r / min for 30 min. Press the resulting mixture onto aluminum foil using a roller press to form a cathode sheet.

[0076] Step 2: In an argon-filled glove box, a coin cell is assembled using lithium metal foil as the negative electrode, lithium hexafluorophosphate as the solute, and a solution formed by dissolving lithium hexafluorophosphate in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7. The concentration of lithium hexafluorophosphate is 1M. Celgard 2500 polypropylene is used as the separator.

[0077] 2. Replace the lithium metal foil in the above-mentioned button cell preparation method with graphite as the negative electrode, and keep other parameters unchanged. Prepare button cells using the composite positive electrode materials prepared in the examples and comparative examples.

[0078] II. Testing Methods

[0079] The performance of the composite cathode materials prepared in the examples and comparative examples was tested. The test items and methods are as follows:

[0080] 1. Electronic conductivity: 80 mg of the composite cathode material prepared in the examples and comparative examples were pressed into cathode sheets with a diameter of 10 mm in a mold under a pressure of 400 MPa. The electronic conductivity was tested using the chronoamperometry at an applied potential of 0.5 V.

[0081] 2. Ionic conductivity: Ionic conductivity was measured by AC impedance spectroscopy. The frequency range of the electrochemical impedance spectroscopy test was 7 MHz to 0.1 Hz, and the AC perturbation amplitude was 10 mV.

[0082] 3. Test the rate performance of the assembled button cells on the battery testing cabinet. The charge and discharge regime is as follows: let stand for 10 hours, and charge and discharge at 0.1C, 0.2C and 3.2C rates at 25℃ respectively to test the rate performance. The discharge cut-off voltage is 0.005V and the charging cut-off voltage is 1.5V.

[0083] The cycle performance of the assembled button cells was tested on the battery test cabinet. The charge and discharge regime was as follows: after standing for 10 hours, the initial charge and discharge capacity at 0.1C was tested at 25℃. After 400 charge and discharge cycles at 5C, the cycle performance was tested. The discharge cutoff voltage was 2V and the charging cutoff voltage was 3.5V.

[0084] The assembled full battery was left to stand for 10 hours. Then, it was tested for cycle performance by charging and discharging 2000 times at 7.5C at 25°C in a battery test cabinet. The discharge cutoff voltage was 2V and the charging cutoff voltage was 3.5V.

[0085] The test results are shown in Tables 1, 2, and 3. Figure 8 and Figure 9 .

[0086] Depend on Figure 8 As shown, the coin cell prepared from the lithium iron silicon niobium oxygen composite cathode material C1 prepared in Example 1 retains a capacity of 82.3% after 400 cycles at 5C rate, while the capacity retention of the lithium iron phosphate sample D1 in Comparative Example 8, which does not have silicon and niobium composite doping modification, is only 24.8%.

[0087] Depend on Figure 9 As shown, the full cell prepared from the lithium iron silicon niobium oxygen composite cathode material C1 prepared in Example 1 retained a capacity of 83.5% after 2000 cycles at a rate of 7.5C. Similarly, the capacity retention of the lithium iron phosphate sample D1 in Comparative Example 8, which did not undergo silicon and niobium composite doping modification, was only 34.9%.

[0088] Table 1. Raw material ratios and conductivity of composite cathode materials prepared in examples and comparative examples.

[0089]

[0090] Table 2 Cycle performance of composite cathode materials

[0091]

[0092] Table 3 Rate performance of composite cathode materials

[0093]

[0094] As shown in Table 1, the total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite in Examples 1-3 was 0.15-0.30:1, and the molar ratio of silicon dioxide to niobium pentoxide was 1:0.12-0.20. The resulting lithium iron silicon niobium oxide composite cathode materials exhibited high electronic and ionic conductivity. In contrast, Comparative Examples 1 and 2 were only doped with Si or Nb. In Comparative Examples 4 and 5, the total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite was 0.12:1 or 0.31:1. In Comparative Examples 6 and 7, the molar ratio of silicon dioxide to niobium pentoxide was 1:0.33 and 1:0.09, respectively. These ratios exceeded the optimal proportions of the present invention, and the resulting composite cathode materials exhibited poor electronic and ionic conductivity, which can be attributed to the presence of poorly conductive silicon dioxide or niobium pentoxide residues on the surface.

[0095] The electronic conductivity and ionic conductivity of the composite cathode material prepared in Example 1 are better than those of the cobalt-doped lithium-rich iron-cobalt-oxygen composite cathode material in Comparative Example 3, indicating that the composite component of the present invention has a higher improvement effect.

[0096] As shown in Tables 2 and 3, the lithium iron phosphate (LiFePO4) silicon-niobium-oxygen composite cathode materials prepared in Examples 1-3 under the conditions of a total molar ratio of silicon dioxide and niobium pentoxide to lithium iron phosphate of 0.15-0.30:1 and a molar ratio of silicon dioxide to niobium pentoxide of 1:0.12-0.20 exhibit superior capacity, cycle performance, and rate performance. In contrast, Comparative Example 1, with only niobium doping, and Comparative Example 2, with only silicon doping, produced composite cathode materials with poorer capacity, cycle performance, and rate performance. This is because the co-doping of Si and Nb creates strong covalent bonds between silicon and oxygen, improving structural stability, suppressing irreversible phase transitions and oxygen precipitation. The inclusion of a small number of pentavalent niobium ions with radii similar to trivalent iron ions in the crystal lattice, along with strong chemical bonds between these ions and oxygen atoms, effectively pins the surrounding oxygen atoms and iron ions, suppressing iron ion displacement during delithiation and further enhancing crystal structure stability.

[0097] As shown in Tables 2 and 3, the lithium iron silane-niobium-oxygen composite cathode material prepared in Example 1 under the conditions of a total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite of 0.22:1 and a molar ratio of silicon dioxide to niobium pentoxide of 1:0.17 exhibits superior capacity, cycle performance, and rate performance. In contrast, the composite cathode materials prepared in Comparative Examples 4 and 5, with a total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite of 0.12:1 or 0.31:1, and in Comparative Examples 6 and 7, with a molar ratio of silicon dioxide to niobium pentoxide of 1:0.33 or 1:0.09, exhibit poorer capacity, cycle performance, and rate performance. It can be seen that when the total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite is not in the range of 0.15-0.30:1, or when the molar ratio of silicon dioxide and niobium pentoxide is not in the range of 1:0.12-0.20, the capacity, cycle performance, and rate performance of the obtained composite cathode material cannot reach the capacity, cycle performance, and rate performance of the composite cathode material prepared when both conditions are met simultaneously. This is because, under the synergistic effect of the total molar ratio of silicon dioxide and niobium pentoxide to lithium iron ferrite of 0.15-0.30:1 and the molar ratio of silicon dioxide to niobium pentoxide of 1:0.12-0.20, the prepared lithium iron silicon niobium oxygen composite cathode material achieves a balance between the strong oxygen-fixing ability of silicon and the excessive internal stress caused by the small effective ionic radius of silicon, and between the framework support ability of niobium and the lattice distortion. This improves the structural stability of the lithium iron silicon niobium oxygen composite cathode material, and the prepared lithium iron silicon niobium oxygen composite cathode material has better capacity, cycle performance and rate performance.

[0098] As can be seen from Comparative Example 3, the capacity, cycle performance and rate performance of the lithium iron silicon niobium oxygen composite cathode material prepared in this application are superior to those of the lithium iron cobalt oxygen composite cathode material prepared by cobalt doping.

[0099] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0101] The present invention has been illustrated with the above embodiments to describe the detailed process flow of the present invention. However, the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium iron silicon niobium oxygen composite cathode material, characterized in that, The preparation method includes mixing lithium ferrite, silicon source, and niobium source in a certain molar ratio, and then calcining them in an inert gas atmosphere to obtain a lithium iron silicon niobium oxygen crystal compound. The lithium iron silicon niobium oxygen crystal compound is then subjected to high-energy ball milling to obtain a lithium iron silicon niobium oxygen composite cathode material. The silicon source is silicon dioxide, the niobium source is niobium pentoxide, the total molar amount of silicon dioxide and niobium pentoxide to lithium ferrite is 0.15-0.30:1, and the molar ratio of silicon dioxide to niobium pentoxide is 1:0.12-0.20; The lithium ferrite is Li5FeO4; The high-energy ball milling process includes: setting the rotation speed to 500-700 r / min forward for 4-8 min, resting for 2-5 min, then reversing the rotation speed to 500-700 r / min for 4-8 min, resting for 2-5 min, alternating between the two, and the ball milling time is 30-50 h; The calcination temperature was 700℃ and the time was 12 hours.

2. The preparation method of the lithium iron silicon niobium oxygen composite cathode material as described in claim 1, characterized in that, The silicon dioxide is amorphous SiO2 with a particle size of 10-100 nm and a specific surface area of ​​90-400 m². 2 / g.

3. The preparation method of the lithium iron silicon niobium oxygen composite cathode material as described in claim 1, characterized in that, The niobium pentoxide has a particle size D50 of 1800-2600 nm and a specific surface area of ​​0.50-0.73 m². 2 / g.

4. The preparation method of the lithium iron silicon niobium oxygen composite cathode material as described in claim 1, characterized in that, The total molar ratio of silicon dioxide and niobium pentoxide to lithium ferrite is 0.22:1, and the molar ratio of silicon dioxide to niobium pentoxide is 1:0.

17.

5. The preparation method of the lithium iron silicon niobium oxygen composite cathode material as described in claim 1, characterized in that, The total molar ratio of silicon dioxide and niobium pentoxide to lithium ferrite is 0.27:1, and the molar ratio of silicon dioxide to niobium pentoxide is 1:0.

20.

6. The method for preparing the lithium iron silicon niobium oxygen composite cathode material as described in claim 1, characterized in that, The high-energy ball milling process includes a ball-to-material ratio of 20-40:1 by mass.

7. A lithium-iron-silicon-niobium-oxygen composite cathode material prepared by the preparation method according to any one of claims 1-6, characterized in that, The nominal composition of the lithium iron silicon niobium oxide composite cathode material is Li5(Fe 0.75+y Si 0.1+x Nb x O4, where 0.03≤x≤0.07, y=0.15-2x; The lithium iron silicon niobium oxide composite cathode material includes amorphous lithium iron silicon niobium oxide compound and lithium niobate nanocrystals, wherein the amorphous lithium iron silicon niobium oxide compound accounts for >95%.

8. A positive electrode plate, characterized in that, The positive electrode includes the lithium iron silicon niobium oxygen composite positive electrode material as described in claim 7.

Citation Information

Patent Citations

  • Carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite as well as preparation method and application thereof

    CN119361866A

  • Gradient doped single-layer coated lithium-rich lithium ferrite material as well as preparation method and application thereof

    CN121439799A

  • Difunctional composite lithium supplement additive as well as preparation method and application thereof

    CN121662994A

  • Lithium-rich lithium ferrite lithium supplement material and preparation method thereof

    CN117558922A

  • Positive electrode material and lithium ion battery

    WO2024103678A1